2006
DOI: 10.1007/s10237-006-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress-driven collagen fiber remodeling in arterial walls

Abstract: A stress-driven model for the relation between the collagen morphology and the loading conditions in arterial walls is proposed. We assume that the two families of collagen fibers in arterial walls are aligned along preferred directions, located between the directions of the two maximal principal stresses. For the determination of these directions an iterative finite element based procedure is developed. As an example the remodeling of a section of a human common carotid artery is simulated. We find that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 50 publications
6
106
0
Order By: Relevance
“…It is not intended to explain the origin of remodeling with its highly complex interactive phenomena between extracellular matrix molecules and living cells at the micro-level, which are still not fully understood. In accordance to previous computational remodeling approaches (Taber and Humphrey 2001;Gleason and Humphrey 2004;Hariton et al 2007;Ricken et al 2007), the present algorithm is stimulated by the stress environment at the macro or tissue level. Traditionally, remodeling algorithms for biological tissues can be classified into stress driven (Taber and Humphrey 2001;Gleason and Humphrey 2004;Hariton et al 2007;Ricken et al 2007) or strain driven formulations (Driessen et al 2004;Kuhl et al 2005;Himpel et al 2008).…”
Section: Introductionmentioning
confidence: 64%
“…It is not intended to explain the origin of remodeling with its highly complex interactive phenomena between extracellular matrix molecules and living cells at the micro-level, which are still not fully understood. In accordance to previous computational remodeling approaches (Taber and Humphrey 2001;Gleason and Humphrey 2004;Hariton et al 2007;Ricken et al 2007), the present algorithm is stimulated by the stress environment at the macro or tissue level. Traditionally, remodeling algorithms for biological tissues can be classified into stress driven (Taber and Humphrey 2001;Gleason and Humphrey 2004;Hariton et al 2007;Ricken et al 2007) or strain driven formulations (Driessen et al 2004;Kuhl et al 2005;Himpel et al 2008).…”
Section: Introductionmentioning
confidence: 64%
“…Indeed, if dF/dP 录 0 represents a normal configuration for the artery in vivo, this can be reached by the deposition of collagen fibers at a certain angle to the circumferential direction. Several scientific papers have reported that remodeling processes may act on the deposition of collagen fibers [27] and that axial stresses may affect these remodeling processes. This view is fully consistent with our model.…”
Section: Implications On the Orientation And Deposition Of Collagen Fmentioning
confidence: 99%
“…In this sense, much effort is directed towards representing remodelling in vascular tissue [40][41][42][43], with a particular focus on the pathological remodelling observed in aortic aneurysm tissue [44][45][46]. The mathematical modelling of the inflammation, proliferation and remodelling phases in ligament tissue has also been addressed [47,48].…”
Section: Introductionmentioning
confidence: 99%